2021
DOI: 10.3390/en14113050
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Diagnosis of the Heat Pipe Solar Collector Malfunction. A Case Study

Abstract: Work was carried out to diagnose irregularities in the operation of a vacuum-tube solar collector. Experimental investigations of the collector were carried out at the solar collector field test stand in the Laboratory of Solar Collectors at the Koszalin University of Technology. The scope of the work included the following: research on thermal efficiency characteristics, research on the temperature distribution on the solar collector manifold, and research on the geometric structure of the heat pipe and filli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The experimental investigations were carried out on a test stand for solar collectors located at the University of Koszalin [34]. The stand was constructed to measure the thermal efficiency of the solar thermal system [35]. The research was conducted between May 2019 and September 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental investigations were carried out on a test stand for solar collectors located at the University of Koszalin [34]. The stand was constructed to measure the thermal efficiency of the solar thermal system [35]. The research was conducted between May 2019 and September 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Such findings are very effective in optimizing consumed power by HVAC systems [18]. Znaczko et al, investigated malfunctions in heat pipe-based solar collectors and discovered the dependency of proper functioning of the heat pipe on geometrical fabrication and the amount of working fluid [19]. In a similar study, Kuczynski et al, investigated the connection between the geometrical aspects and efficiency of flat plate collectors and found that numerical models are very effective in building such correlations [20].…”
Section: Recent Studies On Solar Industrial Process Heatmentioning
confidence: 99%
“…Solar energy is a promising renewable energy source that can be used for facing critical problems like the increasing energy needs [1], fossil fuel depletion [2] and the decarbonization of our society [3]. There are various solar collectors like typical flat plate collectors [4], improved flat plate collectors [5], heat pipe solar collectors [6] and solar passive systems in buildings [7]. Solar concentrating technology is an interesting idea for producing thermal energy at high-temperature levels and so to feed various energy systems with high exergy rates [8].…”
Section: Introductionmentioning
confidence: 99%